2013
DOI: 10.1103/physrevlett.111.135504
|View full text |Cite
|
Sign up to set email alerts
|

Densification and Strain Hardening of a Metallic Glass under Tension at Room Temperature

Abstract: The deformation of metallic glasses involves two competing processes: a disordering process involving dilatation, free volume accumulation, and softening, and a relaxation process involving diffusional ordering and densification. For metallic glasses at room temperature and under uniaxial loading, disordering usually dominates, and the glass can fail catastrophically as the softening process runs away in a localized mode. Here we demonstrate conditions where the opposite, unexpected, situation occurs: the dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 33 publications
9
89
0
1
Order By: Relevance
“…(4) demonstrates the role of stress gradients in the incubation of shear bands in MGs, because that the initiation of shear banding is always attributed to the stress concentrators of MGs, namely, local defects or the sites where free volume accumulates [1], where both scenarios associate with stress gradients. Stress gradients enhanced shear banding propensity of MGs have widely been proved, such as indentation where severe stress gradients beneath the indenter trigger large amounts of shear bands [47], the stress gradients introduced by shot peening [48] or drawing [49] leading to pronounced shear bands proliferation and the stress gradients introduced via adjusting the shape of MGs, like the aspect ratio [50,51], the notch [52] and the unparalleled ends Table 1 Shear banding susceptibility of several metallic glasses. [53].…”
Section: Resultsmentioning
confidence: 99%
“…(4) demonstrates the role of stress gradients in the incubation of shear bands in MGs, because that the initiation of shear banding is always attributed to the stress concentrators of MGs, namely, local defects or the sites where free volume accumulates [1], where both scenarios associate with stress gradients. Stress gradients enhanced shear banding propensity of MGs have widely been proved, such as indentation where severe stress gradients beneath the indenter trigger large amounts of shear bands [47], the stress gradients introduced by shot peening [48] or drawing [49] leading to pronounced shear bands proliferation and the stress gradients introduced via adjusting the shape of MGs, like the aspect ratio [50,51], the notch [52] and the unparalleled ends Table 1 Shear banding susceptibility of several metallic glasses. [53].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is reported that the densification of metallic glasses under the effect of applied stress, which is exactly the very mechanical annealing effect discussed in our work could probably be the dominant workhardening mechanism for metallic glasses and plays a key role in the ductility of metallic glasses. 33,62 Consequently, our work might provide important clues for uncovering the underlying work-hardening mechanism stemming from the coalescence of the negative type and the positive type of free volume in metallic glasses and will enhance the current understanding on the ductility of metallic glasses. More works on these issues will impart us more thorough understanding on both the structure and the properties of metallic glasses.…”
Section: B Stress-temperature Scaling In Glass Transitionmentioning
confidence: 99%
“…The existence of a "mechanical annealing" effect of stress on metallic glasses similar to the well studied thermal annealing effect [30][31][32] of temperature, i.e., flow stress induced free volume decrease, is yet to be experimentally confirmed to solidify the basis of the stress-temperature scaling. On the other hand, the underlying mechanical annealing process would probably be the dominant work-hardening mechanism in metallic glasses [33][34][35] due to the lack of intersections between crystal defects (e.g., dislocations and grain boundaries). Proving the existence of the mechanical annealing effect would improve the current understanding on the ductility of metallic glasses.…”
mentioning
confidence: 99%
“…To alleviate this problem, many studies have been done recently to enhance their plasticity [4][5][6][7][8][9][10] by various methods such as introduction of a second phase, introduction of shear bands, and control of free volume.…”
Section: Introductionmentioning
confidence: 99%